The Emerging Role of Exosomes in Cancer Chemoresistance - Li, Jing; Gao, Na; Gao, Zhengfan; Liu, Wei; Pang, Bairen; Dong, Xingli; Li, Yong; Fan, Tianli (Frontiers in Cell and Developmental Biology, 2021)
Chemoresistance presents an impending challenge in cancer treatment. In recent years, exosomes, a subtype of extracellular vesicles with a diameter of 40–150 nm present in the bloodstream and other bio-fluids, have attracted increasing interest. Exosomes contain proteins, nucleic acids, and lipids, which act as important signaling molecules. Many reports indicate that exosomes play critical roles in chemoresistance through intercellular interactions, including drug removal from cells, transfer of drug resistance phenotypes to other cancer cells, and the increase in plastic stem cell subsets. Exosomes can reflect the physiological and pathological state of parent cells. Owing to their elevated stability, specificity, and sensitivity, exosome can serve as biomarkers in liquid biopsies to monitor cancer chemoresistance, progression, and recurrence. This review summarizes the exosome-mediated mechanism of cancer chemoresistance, as well as its role in reversing and diagnosing chemoresistance. The scientific and technological challenges and future applications of exosomes are also explored.